Andean agriculture and hand tools: A qualitative approach of exploration of needs, barriers, and opportunities for innovation - Liliana Cruz-Ausejo; José del Carmen Abad Castillo; Claudia Cardenal; MD Zahid Hasan; Amit Bhattacharya; Jerome T. Galea (PLoS ONE, 2026)
Peruvian Andean agriculture primarily consists of subsistence activities that rely on traditional methods. Rural farmers use locally made hand tools, often designed without technical or ergonomic considerations, increasing the risk of musculoskeletal disorders. This study examined farmers’ views, needs, barriers, and support in hand tool design, and how they assess satisfaction with tools during potato harvesting. A qualitative study using a phenomenological design was conducted using semi-structured interviews with 13 rural farmers from Yanaca, Apurímac, Peru. A total of 25 interviews were conducted, audio-recorded, transcribed verbatim, and analyzed via a mixed coding strategy. Data was organized using a thematic approach and triangulated to validate coding. The results from the first guide were organized into five themes: task, human, product, qualitative and environmental. Some aspects such as social and techniques aspects for adopting hand tools emerged as well as enablers like economic accessibility, similarity to traditional tools. Six themes emerged from second guide covering tools conditions for efficient use, pre-work preparation, evaluation of the tool, consequences of a deficient tool, accumulated experience and appropriation; and family and gender dynamics. We found that hand tools used in high-Andean agriculture are shaped by technical features such as weight and handle size, and external aspects like climate effect and cultural familiarity, while material limitations, rough handle surface or inadequate tool size can act as barriers. In addition, efficiency of tools during work, preparation like a sharpened tip, fit between components head and handle, local maintenance facilitates farmers’ satisfaction. These findings suggest that agricultural hand tool design should go beyond technical aspects to incorporate cultural and practical perspectives.